La resistencia aeróbica en estudiantes del quinto de secundaria de la Institución Educativa Simón Bolivar Nº 60188, Iquitos 2022 - Dahua Yaicate, Konnie Stefany (2025)
This study begins with the question: ¿What is the level of aerobic resistance in students of the fifth year of secondary school at the Simón Bolívar Educational Institution Nº 60188 Iquitos 2022?, and the general objective is formulated: to describe the level of aerobic resistance in students of the fifth year of secondary school of the Educational Institution. It is designed taking into account the type of study, which is descriptive with field observation, transversal because it is a single measurement and univariable. To record data, the Cooper aerobic resistance test was used, validated by experts and applied through the observation technique. The total number of students, made up of 155 participants, constituted both the population and the sample of the study. As results after carrying out the global analysis of the research, it is understood that the level of aerobic resistance of the 155 (100.0%) fifth secondary students of the Simón Bolívar Educational Institution No. 60188, is regular at 60.0% (n= 93), it is bad in 20.6% (n=32) and it is excellent and good in 9.7% (n=15).